Kajian Higiene Sanitasi Makanan Minuman di Instalasi Gizi Rumah Sakit Jiwa Daerah Dr. R. M. Soedjarwadi, Klaten - erni Cahyani Putri; Sigid Sudaryanto; Purwanto Purwanto (Sanitasi: Jurnal Kesehatan Lingkungan, 2016)
Hospitals are health care institution that organizing comprehensive individual health services thatprovide inpatient, outpatient, and emergency services. On the other hand, based on it’s activities,a hospitals can be a place of disease spreading and potential as a source of environmental pollution and health disturbance. To avoid those risks and to improve the high-quality services, it isneeded to implement environmental health efforts, one of which is good food and beverage hygiene and sanitation practices. The purpose of this study was to know the action of those hygieneand sanitation measure at the Nutrition Installation of the Klaten’s Dr. R. M. Soedjarwadi localMental Hospital. The objects of this descriptive study comprised of: groceries selection, food ingredients storage, food processing, cooked food storage, food delivery, and food service. As therespondents were the chief in-charge of the Nutrition Installation and 21 food processing officers.To collect the data, check list form and interview guide were used. Based on the observations itwas found that the score of the hygiene and sanitation practices was 3140 or 92.08 % of the maximum value. Some findings that have not meet the standard were: six out of 10 officers did notuse head-gear, temperature of food store-room (26,03 oC), humidity of food store-room (68.4 %),lighting of food processing site (80 lux), and the facilities for food warming did not fulfill the requirement. In general, it can be concluded that the implemnetation of the food and beverage hygiene and sanitation practices in the hospital is proper